(untitled) (Comprehensive Journal of Science, 2025)
The study aims to identify the role of the organizational environment in managing engineering projects, with a field application on engineering companies in Benghazi. The research adopted a descriptive-analytical approach, using a questionnaire distributed to 200 participants, including engineers, project managers, and administrative staff. It examined the impact of the main components of the organizational environment administrative structure, organizational culture, leadership, and internal communication on project management efficiency. The findings revealed a strong positive correlation between these factors and the success of engineering projects, indicating that effective leadership and clear internal communication are among the most influential elements supporting performance. However, the study also identified challenges related to adherence to schedules and budgets due to weaknesses in planning and organization. The study concluded that enhancing flexible organizational structures, fostering a culture of innovation and discipline, and activating digital communication channels are essential to improving performance and increasing project success rates.